Therapeutic and Preventive Effects of Aqueous Extract of Date Palm (Phoenix dactylifera L.) Pits on Ethylene Glycol-Induced Kidney Calculi in Rats - Mohammadparast Tabas, Pouria; Aramjoo, Hamed; Yousefinia , Ali; Zardast, Mahmoud; Abedini, Mohammad Reza; Malekaneh, Mohammad (Urology Journal, 2021)
Introduction: Urinary tract stones are one of the most common diseases in the urinary tract. Lack of kidney stone treatment causes irreparable damages to the kidneys, which has many harmful effects. Date palm pits are recommended in traditional medicine as an effective drug in the treatment of kidney stones. The aim of this study was to investigate the effect of aqueous extract of date palm pits on kidney stones induced by ethylene glycol in male rats. Methods: In this study, 40 rats were classified into five groups (n = 8), including the healthy group receiving normal water, the negative control group, the therapeutic groups with doses of 150 mg/kg and 300 mg/kg, and the prevention group with a dose of 300 mg/kg. In order to induce kidney stones, ethylene glycolated water (1%) was used as drinking water in the studied groups. Blood and urine of rats were collected on days 14 and 28 of the study to assess urinary parameters of calcium, creatinine, uric acid and phosphorus, and serum parameters of blood urea nitrogen, creatinine, uric acid, calcium, and phosphorus. Also, the kidneys of rats were removed from the body on day 28 of the study and were given to a pathologist for examination. Results: Results of serum parameters shows that the use of date palm pits extract in the treatment and prevention groups with a dose of 300 mg/kg significantly (P < .05) has reduced the levels of blood urea nitrogen, uric acid, calcium, creatinine and phosphorus. Also, the results of urinary parameters show that the use of the extract caused a significant decrease (P < .05) in creatinine, uric acid and calcium in the prevention group and a significant decrease (P < .05) in creatinine and uric acid in the therapeutic group with a dose of 300 mg/kg. Pathological results show a decrease in the number and size of calcium oxalate crystals in renal tubules in the treatment and prevention groups in a dose-dependent manner. Conclusion: The results of this study showed that the use of aqueous extract of date palm pits has been effective in the treatment and prevention of kidney stones induced by ethylene glycol in rats.